Pantethine therapy dramatically rescues end‐stage failing heart in a patient with deficiency of coenzyme A biosynthesis - Goetz, Violette; Lefort, Bruno; Barth, Magalie; Gueguen, Naïg; Bris, Céline; Blanchard, Emmanuelle; Benz‐de Bretagne, Isabelle; Blasco, Hélène; Tardieu, Marine; Labarthe, François (ESC Heart Failure, 2025)
Despite intensive pharmacological cardiac support [epinephrine, norepinephrine, angiotensin-converting enzyme (ACE) inhibitor, beta-blocker, diuretics, milrinone and repeated infusions of the calcium sensitizer levosimendan], cardiac situation remains precarious (Figure 2) and the patient experienced 2 months later a second cardiac arrest successfully resuscitated. Plasma levels of creatine kinase (median value 908 U/L, range 250–114 830, N < 310) and of ammonia (median value 85 μmol/L, range 26–129, N < 40) remained fluctuating. Because of recurrent vomiting, a gastroparesis was confirmed by gastric scintigraphy and jejunal tube feeding was required. [...]exome sequencing led to the identification of a new homozygous mutation in the PPCS gene (c.727G > C, p. Ala243Pro) categorized as highly deleterious by prediction tools. Currently, six patients from three unrelated families have been reported with PPCS deficiency, all of them with a predominantly cardiac presentation including dilated cardiomyopathy and various degrees of heart failure.3,5 Two of these patients had a severe neonatal presentation, very similar of our patient. Besides dilated cardiomyopathy, both experienced acute life-threatening events with heart failure, recurrent episodes of increased plasma levels of creatine kinase, hyponatremia and hypokalaemia, and finally died at 3 and 4 months of age.